On the Study of an Initial Value Problem for a Second Order Differential Equation Set in a Singular Cylindrical Domain - Belkacem, Chaouchi; Kostic, Marko (Sarajevo Journal of Mathematics, 2022)
We will investigate an initial value problem for a second order differential equation set in a singular cylindrical domain Π . The existence, uniqueness and maximal regularity results are obtained for the classical solutions by using the semigroup theory. The study is performed in the framework of little Hölder space h^2σ (Π ) with 0<2σ <1.